Doñana: an experience in spanish wetlands - Mora-Olivo, Arturo (Universidad Autónoma de Tamaulipas, 2011)
Describes the research experience of the authors that participated in the XVII Conference on Countryside Biogeography of Spain. This year, this event took place in one of the most important wetland reserves for biodiversity, geographical location and condition, the Doñana nature reserve. Through the interaction of a multidisciplinary team, the major characteristics of two study sites where described, from the point of view of flora and fauna. The application of novel sampling techniques enabled learning and exchange of ideas between researchers and students from different countries. The participation of Mexicans in this event influenced the organizing committee to propose to the Mexican reserves Heaven as a study area for the next biogeography generation.